1984
DOI: 10.1139/e84-141
|View full text |Cite
|
Sign up to set email alerts
|

A tectonic window in central Newfoundland? Geological evidence that the Appalachian Dunnage Zone may be allochthonous

Abstract: In the Through Hill area of central Newfoundland, mafic to ultramafic complexes, which preserve varying amounts of ophiolite stratigraphy, mark the trace of a major fault zone that outcrops in a roughly elliptical pattern. The major, northeasttrending axis is about 60 km and the shorter axis is about 30 km in length. The most complete ophiolite stratigraphy is preserved in the Coy Pond and Pipestone Pond complexes, which have steep dips and face east and west, respectively, outwards from the centre of the elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…This Exploits cover is everywhere characterized by the Celtic Fauna (Neuman, 1967(Neuman, , 1984Wonderley and Neuman, 1984). Significant is that this same Exploits cover also unconformably overlies the Early Ordovician ophiolitic rocks of the Exploits Subzone in Newfoundland (Kennedy and McGonigal, 1972;Colman-Sadd and Swinden, 1984) and probably also the Avalon Zone rocks of the Hermitage Flexure in southern Newfoundland (Chorlton, 1978;Dunning and O'Brien, 1989). Hence, the Middle Ordovician Exploits cover was interpreted as an overstep sequence (Williams and Piasecki, 1990; van Staal and Williams, 1991) deposited after early Arenig (Penobscot) obduction of the ophiolites on the Gander clastics, an interpretation confirmed through dating a stitching pluton (Partridgeberry Hills Granite: 474 +6/-3 Ma) by .…”
Section: Extent and Geological Setting Of The Gander Zonementioning
confidence: 97%
See 1 more Smart Citation
“…This Exploits cover is everywhere characterized by the Celtic Fauna (Neuman, 1967(Neuman, , 1984Wonderley and Neuman, 1984). Significant is that this same Exploits cover also unconformably overlies the Early Ordovician ophiolitic rocks of the Exploits Subzone in Newfoundland (Kennedy and McGonigal, 1972;Colman-Sadd and Swinden, 1984) and probably also the Avalon Zone rocks of the Hermitage Flexure in southern Newfoundland (Chorlton, 1978;Dunning and O'Brien, 1989). Hence, the Middle Ordovician Exploits cover was interpreted as an overstep sequence (Williams and Piasecki, 1990; van Staal and Williams, 1991) deposited after early Arenig (Penobscot) obduction of the ophiolites on the Gander clastics, an interpretation confirmed through dating a stitching pluton (Partridgeberry Hills Granite: 474 +6/-3 Ma) by .…”
Section: Extent and Geological Setting Of The Gander Zonementioning
confidence: 97%
“…1) lies in northeastern Newfoundland near the town of Gander (Kennedy and McGonigal, 1972;Kennedy, 1976). Regional mapping subsequently showed that the distinct clastic rocks of the Gander area could be extrapolated into southern and southwestern Newfoundland (Brown and Colman-Sadd, 1976;Williams, 1979;Colman-Sadd, 1980) and into structural basement windows in the Exploits Subzone of the Dunnage Zone of central Newfoundland (Colman-Sadd and Swinden, 1984;Williams et al, 1988). Detrital titanite and intrusive granites show that the Gander rocks are younger than ca.…”
Section: Extent and Geological Setting Of The Gander Zonementioning
confidence: 99%
“…Post-Middle Ordovician thrust faults were also reported from the Exploits Subzone by Kay and Williams (1963), Jacobi and Schweickert (1976) Kidd (1977) Blackwood (1979Blackwood ( , 1982, Pajari er al. (1979), Colman-Sadd (1980), Thurlow (1981), Colman-Sadd and Swinden (1984), van der Pluijm, (1984van der Pluijm, ( , 1986van der Pluijm, ( ,1987. van der Pluijm and van Staal(1988) Kusky (1985) Kusky and Kidd (1985), Elliott (1985a); and Elliott and Williams (1988).…”
Section: Regional Extent and Timing Of Southeastward Directed Thrustingmentioning
confidence: 99%
“…Trilobite, brachiopod and graptolite localities have received most attention, and precise stratigraphic data generally in dicating Early and Middle Ordovician ages have been ob tained (e.g., Colman-Sadd and Swinden, 1984;Boyce, 1987;Boyce eta l., 1988Boyce eta l., , 1993aWilliams, 1991Williams, , 1993Williams et al, 1992). Localities containing mainly cririoids, bryozoa, and corals and a few brachiopods have only rarely been ex amined in detail.…”
Section: Introductionmentioning
confidence: 99%